Species richness and genetic diversity of the acropora fauna along the a North-West Coast of Sabah - Rolando Robert (2017)
Staghorn corals (Acropora Oken, 1815) are the most abundant reef-building corals in Sabah but current knowledge on their species richness is deficient at many localities while baseline data on their genetic diversity are non-existent. In this study, 122 staghorn coral individuals were sampled from coral reefs around Pulau Tiga Park, P. Mantanani, and P. Banggi, Sa bah using SCUBA, following which taxonomic assignment was conducted by examining their skeletal morphology. Afterwards, 50 ( N) representative individuals were subjected to DNA barcoding using nucleotide sequences of the partial cytochrome c oxidase subunit-I ( COi) and cytochrome b ( CYB), and multi-locus microsatellite genotyping using 11 universal markers containing tri-, tetra-, penta-, and hexa-nucleotide repeat motifs. A total of 33 different species were identified from the three localities of which 14 occur in P. Tiga Park, 26 in P. Mantanani, and 22 in P. Banggi. Two species, Acropora dendrum and A. desalwii, are reported for the first time in Sabah. Meanwhile, the 50 individuals barcoded and genotyped represent the 33 identified species and a morphotype designated as Acropora sp. Substitution rate of the staghorn coral CYB (mean p-distance: 0.38%) was faster than the substitution rate of the COi (mean p-distance: 0.24%), while the value recorded for the COI-CYB was the average of these two rates (mean trdistance: 0.32%). Subsequently, haplotype diversity (Hd) with respect to the CYB sequences (number of haplotypes: 36; Hd ± S.D. = 0.91 ± 0.04) was higher than that with respect to the COi sequences (number of haplotypes: 25; Hd ± S.D. = O. 73 ± 0.07). The number of COI-CYB haplotypes was the highest at 42 (Hd ± S.D. = 0.97 ± 0.02), as more nucleotide substitutions were captured. Consequently, the phylogeny of the staghorn corals inferred using the COI-CYB sequences exhibited the best resolution but all the trees reconstructed shared a common multifurcating topology, which suggested a polyphyletic evolutionary pattern among the staghorn corals. The discriminatory power of the DNA barcodes currently employed were therefore inadequate for intrapopulation studies, which underlined the potential of the hypervariable microsatellite markers for such investigations. The microsatellite markers used in this study were polymorphic with number of alleles ranging from seven to 23 per locus (mean = 13.5). Estimates of genotypic diversity suggested a state of heterozygote deficit within the Sabah population as the level of observed heterozygosity (Ho = 0.39 ± 0.14) was over two-fold lower in contrast to the levels expected (He = 0.84 ± 0.08; Nei's He = 0.83 ± 0.08). The lack of genotypic diversity within the Sabah staghorn corals could signal lowered adaptive capacity of the population to extreme changes in their environment that warrants urgent conservation measures. The results presented here further add to current knowledge on the species richness of staghorn corals in Sabah and represent the first quantitative baseline data on their genetic diversity.